PERLINDUNGAN HUKUM BAGI KONSUMEN E-COMMERCE MENURUT UNDANG – UNDANG NO.8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Ria Sintha Devi; Feryanti Simarsoit (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
Trading activities in the community have developed very rapidly. This is influenced by the development of trade using internet-based technology known as Electronic Transactions (e-commerce). E-commerce can be interpreted as trading on the internet. For this reason, this research will find out about the arrangements regarding consumer protection in Indonesia, the implementation of consumer protection in electronic transactions at PT.Solusi E-commerce Global and about the resolution of consumer disputes on electronic transactions at PT. Global E-commerce solutions. The study was conducted using a combination of normative legal research and sociological legal research. Sources and types of data used are primary data and secondary data. Data collection techniques use literature studies and also through direct interviews with relevant companies. The conclusion that can be drawn in this study is that based on Law No.8 of 1999 concerning Consumer Protection has provided guarantees and protection of consumer rights in Indonesia. PT.Solusi E-commerce Global as a business actor has contractual and statutory responsibilities towards consumers or clients and also guarantees the fulfillment of consumer rights as agreed in the contracts they have previously agreed upon and also as contained in the UUPK. So far, PT. Global E-commerce Solution has never faced a consumer dispute, and if there are only complaints from consumers, then it will be settled amicably by both parties at that time.